A case of pituitary adenoma presenting with normal hormone levels - Surya, G. S. Sanjay; Venugopalan, Priya; Hanumanram, Gowtham; Mithra, Deepthi (International Journal of Advances in Medicine, 2022)
We report a case of pituitary adenoma with normal hormone levels in a 34-year-old female. She presented to OP with headache, milky discharge from nipples and secondary amenorrhea with transient loss of vision. Patient had hyperprolactinemia with normal levels of all other pituitary hormones. MRI revealed space occupying lesion in sellar and suprasellar region. Neurological consultation suggested Rathke’s cyst/ craniopharyngioma/ macroadenoma. Excised lesion was diagnosed as pituitary adenoma during histopathological analysis.